When global scripts do not resonate: international minority rights and local repertoires of diversity in southern Turkey - Ozgen, Zeynep; Koenig, Matthias (Qualitative sociology, 2022)
Under what conditions do global scripts resonate among ordinary people? Neo-institutional world polity theory has tended to sideline this question by privileging macro-comparative explanations of states’ adoption and social movement activists’ framing of global scripts. Adopting a negative case approach, we draw on concepts from cultural sociology to explain why global scripts fail to resonate among ethno-religious minorities in Antakya, Turkey. Antakya has been exposed intensely to global minority rights and multiculturalism discourses; it has been targeted by various ethnic movement activists, and its diverse population has long experienced stigma and discrimination stemming from Turkey’s model of nationhood. Yet, ordinary people there have seldom utilized global diversity scripts in their everyday struggles for recognition. Drawing on longitudinal qualitative fieldwork between 2004 and 2015, we find that global scripts fail to match people’s cultural schemas of perceiving and reproducing boundaries—their local repertoires of diversity—due to a deep-seated ambivalence toward the category of “minority.” This lack of resonance potentially weakens popular support for substantial policy reforms advancing minority rights and is one among several factors explaining why Turkey’s turn from an exclusionary to an inclusionary model of nationhood has remained largely ceremonial.